2020
DOI: 10.3389/fneur.2020.593950
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Transcranial Direct Current Stimulation in Glioma Patients: A Proof of Concept Pilot Study

Abstract: Background: Transcranial direct current stimulation (tDCS) has been used extensively in patient populations to facilitate motor network plasticity. However, it has not been studied in patients with brain tumors. We aimed to determine the feasibility of a preoperative motor training and tDCS intervention in patients with glioma. In an exploratory manner, we assessed changes in motor network connectivity following this intervention and related these changes to predicted electrical field strength from the stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…One of the earliest studies was [101] that reported a significant positive correlation between tDCS-induced electric fields and changes in task-based fMRI data(post tDCS minus pre tDCS) in a single subject. Significant associations between electric fields and changes in functional activity/connectivity has been also reported in some other previous studies [50][51][52]54]. This information would also help to determine where and to what extent targeted brain regions should be stimulated (e.g., in FPS) in a group of participants (e.g., SUD group).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 65%
See 1 more Smart Citation
“…One of the earliest studies was [101] that reported a significant positive correlation between tDCS-induced electric fields and changes in task-based fMRI data(post tDCS minus pre tDCS) in a single subject. Significant associations between electric fields and changes in functional activity/connectivity has been also reported in some other previous studies [50][51][52]54]. This information would also help to determine where and to what extent targeted brain regions should be stimulated (e.g., in FPS) in a group of participants (e.g., SUD group).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 65%
“…Previous fMRI-computational head modeling studies reported relationships between computed field measures (e.g., electric field strength) and functional outcomes [47,50]. Results revealed that electric field intensity generated by a specific electrode montage correlated with changes in functional activity/connectivity patterns in targeted brain areas [50][51][52][53][54][55]. Therefore, determining the ideal configuration of electrodes to optimally target a specific brain function and distinct network nodes is important and choice of suited stimulation montage and dose to enhance cortico-cortical coupling is not straightforward [45].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [ 29 ] used ROAST to model N = 8 glioma patients in their study of TES feasibility on these patients. They showed that patient-specific modeling of electric field in the presence of tumor may contribute to understanding the dose-response relationship of this intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Note that for those studies that involved subjects with pathological head anatomies (e.g., tumor or lesion), customized segmentation was performed and integrated into the ROAST pipeline to account for these anatomies [ 25 , 29 ]. This is because the segmentation function in ROAST [ 116 ] was developed for normal head anatomy only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation